On Stockhausen's Solo(s): Beyond Interpretation. - CANCINO, JUAN PARRA; MULDER, JOHANNES (Leonardo Music Journal, 2018)
Using Karlheinz Stockhausen's Solo für Melodieinstrument und Rückkopplung (1965--1966) as a starting point, the authors investigate the affect and effect of technological transference when reproducing historical repertoire with live electronics. A suggestion of technical transparency often accompanies digital sound technologies; we aim to challenge this notion. We argue that the coloring that emerges with digital media can (and perhaps should be) used to inject new life into, and ask new questions of, the works that are being preserved.